The rise and fall of Russia's Far Eastern republic, 1905-1922: nationalisms, imperialisms, and regionalisms in and after the Russian empire - Sablin, Ivan (Routledge Taylor & Francis Group, 2019)
Left-liberal nationalism and self-organization east of baikal, 1905-1916 -- Post-imperial particularisms in the Russian Far East, 1917-1919 -- Nationalisms and the making of the Far Eastern republic, 1920 -- The Far Eastern republic and the Priamur state formation, 1921 -- Competing nationalisms and sovietization in the Russian Far East, 1922
Includes bibliographical references and index
Keywords: Russian Far East (Russia) -- History -- Autonomy and independence movements; Dalʹnevostochnai︠a︡ Respublika -- History; Russian Far East (Russia) -- History -- 1917-1921; Geschichte 1905-1922; Fernöstliche Republik